Baking illustrated : a best recipe classic (Brookline, Mass. : America's Test Kitchen, 2004)
A comprehensive baking reference offers 350 recipes for baking pies, breads, cookies, cakes, pastry, crisps, cobblers, and tarts.
Chapter 1: Quick breads, muffins, biscuits, and scones -- Chapter 2: Yeast breads and rolls -- Chapter 3: Pizza, focaccia, and flatbread -- Chapter 4: Pies and tarts -- Chapter 5: Pastry -- Chapter 6: Crisps, cobblers, and other fruit desserts -- Chapter 7: Cakes -- Chapter 8: Cookies, brownies, and bar cookies.
Includes index.
Keywords: Baking; Desserts